ANALISIS KELAYAKAN USAHA PADA UMKM WM MIROSO BU WARMAN BANYUBIRU: ASPEK SDM DAN LEGALITAS - Fa'iza Annisa Salsabila; Khoirotun Nadhiroh; Sania Camilia Putri; Mokhammad Khukaim Barkhowa (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
Micro, small, and medium enterprises (MSMEs) have an important role in supporting the economy, especially in creating employment opportunities and improving community welfare. However, MSMEs still face various challenges, particularly in the aspects of human resources and business legality, which may affect business sustainability. This study aims to analyze the business feasibility of UMKM WM MIROSO Bu Warman banyubiru by focusing on human resource and business legality aspects.  This study used a descriptive qualitative approach. Data were obtained through interviews with business owners and employees, questionnaires to customers, and direct observation of business activities. The results showed that the human resource aspect was considered quite good. The number of employees was sufficient to support operational activities, employees had adequate skills, and the quality of service provided was considered good by customers in terms of responsiveness, assurance, and empathy. Nevertheless, there were still several shortcomings, such as occasional service errors and less optimal cleanliness conditions. In terms of business legality, the business already possessed a halal certificate but had not yet obtained a Business Identification Number (NIB) and other business permits. Overall, the business was considered feasible to operate and develop because it had adequate human resources and service quality. However, improvements were still needed in terms of cleanliness, service accuracy, and completion of business legality to support sustainable business development